2014
DOI: 10.1007/s00449-014-1270-x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase biosensor based on multi-walled carbon nanotubes-SnO2-chitosan nanocomposite

Abstract: A sensitive amperometric acetylcholinesterase (AChE) biosensor was developed based on the nanocomposite of multi-walled carbon nanotubes (MWCNTs), tin oxide (SnO2) nanoparticles and chitosan (CHIT). Acetylcholinesterase (AChE) and Nafion were immobilized onto the nanocomposite film to prepare AChE biosensor for pesticide residues detection. The morphologies and electrochemistry properties of the surface modification were investigated using cyclic voltammetry, differential pulse voltammetry, and scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The adherence of the enzyme molecules onto electrode surfaces without denaturing the enzyme or blocking the active site has been a critical challenge for researchers. Various strategies have been used to immobilise AChE onto the electrode surface, including adsorption [66], entrapment [67,68] and cross-linking [69,70] amongst others. In an extensive study of immobilisation techniques Pohanka et al [71] concluded that glutaraldehyde cross-linking was the preferred method and has proved to be a useful method for a range of electrode materials, such as gold [72], platinum [73] and carbon SPEs [74].…”
Section: Organophosphate (Op) Sensingmentioning
confidence: 99%
See 3 more Smart Citations
“…The adherence of the enzyme molecules onto electrode surfaces without denaturing the enzyme or blocking the active site has been a critical challenge for researchers. Various strategies have been used to immobilise AChE onto the electrode surface, including adsorption [66], entrapment [67,68] and cross-linking [69,70] amongst others. In an extensive study of immobilisation techniques Pohanka et al [71] concluded that glutaraldehyde cross-linking was the preferred method and has proved to be a useful method for a range of electrode materials, such as gold [72], platinum [73] and carbon SPEs [74].…”
Section: Organophosphate (Op) Sensingmentioning
confidence: 99%
“…Carbon remains the most common electrode material (Table 7) and has been used in the detection of OPs in sub-ppb concentrations [63,67,73,74], although gold [72] and platinum [75] have also been successfully used in the analysis of ppb levels of OPs.…”
Section: Organophosphate (Op) Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al developed a sensitive amperometric AChE biosensor based on nanocomposite of multi-walled carbon nanotubes, tin oxide nanoparticles and chitosan. This biosensor was used for pesticide residue detections 156 .…”
Section: Chitosanmentioning
confidence: 99%